Prevalence of supernumerary teeth among a sample of patients attending college of dentistry in Erbil, Iraq - Fighan Jalal Hussein; Heran Ibrahim Hassan; Alaa Mahmud Mustafa (Erbil Dental Journal)
Background and Objectives: A supernumerary tooth is an additional tooth to the normal series and can be located in almost any region of the dental arch. The objective of the study was to investigate the prevalence of supernumerary teeth and the distribution of the cases according to the demographic data and characteristics among patients attending a College of Dentistry in Erbil, Iraq.